Typology of Public Service Innovations in Radio Station Permits for Fishermen Through the Maritime on The Spot Program (Study at the Directorate General of Postal and Information Resources and Equipment) - Yulli Fitria; Juwono, Vishnu (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
This study examines the typology of public sector innovations for the Maritime On The Spot (MOTS) program to lessen the interference to aviation radio frequencies that fishing communities cause by using unauthorized radio communication equipment. 35 Technical Implementation Units of the Directorate General of Postal and Informatics Resources of the Ministry of Communication and Information Technology provide ball pick-up public services to fishing communities at fishing ports. This program aims to address the 95% of the fishing sector that still lacks radio communication permits for fishing and awareness of radio communication procedures at sea. Socialization and technical assistance are necessary to get Fisheries Radio Communication Permits (IKRAN). Using a qualitative methodology to collect data through interviews, documentation, and literature studies, this research finds that MOTS innovation can help the fishing sector and fishermen overcome interference related to fishermen's radio communications with the aviation service. It was carried out in 2023.